The usage of pelvimetry to predict dystocia in cattle - Hiew, Mark Wen Han; Constable, Peter D. (Veterinary Association Malaysia, 2015)
Pelvimetry is the measurement of the dimensions of the pelvis, measured internally or externally, and is typically conducted with the aid of a pelvimeter. Intrapelvic dimensions, namely the intrapelvic height and width, are used to calculate pelvic are a which has a moderate to high degree of heritability. Pelvic area measurements are associated with calving difficulty and have been used by producers to select for heifers to be included in their breeding herd.